Breadth of humoral immune responses to the C-terminus of the circumsporozoite protein is associated with protective efficacy induced by the RTS, S malaria vaccine. Issue 6 (5th February 2021) - Chaudhury, Sidhartha; MacGill, Randall S.; Early, Angela M.; Bolton, Jessica S.; King, C. Richter; Locke, Emily; Pierson, Tony; Wirth, Dyann F.; Neafsey, Daniel E.; Bergmann-Leitner, Elke S.
Highlights: Development of novel multiplex assay to test antigen variants without antigenic competition. Malaria circumsporozoite protein variants identified in field studies for vaccine evaluation. Breadth of antibody reactivity to vaccine variant antigens predicts protection from infection. Data point to critical role of C-terminal Circumsporozoite antibodies in protection. Reactivity pattern to antigenic variants reflects sequence divergence. Structural modeling and epitope prediction identified putative non-protective epitopes. Abstract: The circumsporozoite protein (CSP) is the main surface antigen of malaria sporozoites, a prime vaccine target, and is known to have polymorphisms in the C-terminal region. Vaccines using a single allele may have lower efficacy against genotypic variants. Recent studies have found evidence suggesting the efficacy of the CSP-based RTS, S malaria vaccine may be limited against P. falciparum CSP alleles that diverge from the 3D7 vaccine allele, particularly in this polymorphic C-terminal region. In order to assess the breadth of the RTS, S-induced antibody responses against CSP C-terminal antigenic variants, we used a novel multiplex assay to measure reactivity of serum samples from a recent RTS, S study against C-terminal peptides from 3D7 and seven additional CSP alleles that broadly represent the genetic diversity found in circulating P. falciparum field isolates. We found that responses to the variants showed, on average, a 30-fold reduction in reactivity relative to the vaccine-matched 3D7 allele. The extent of this reduction, ranging from 21 to 69-fold, correlated with the number of polymorphisms between the variants and 3D7. We calculated antibody breadth of each sample as the median relative reactivity to the seven CSP variants compared to 3D7. Surprisingly, protection from 3D7 challenge in the RTS, S study was associated with higher C-terminal antibody breadth. These findings suggest CSP C-terminal-specific avidity or fine-specificity may play a role in RTS, S-mediated protection and that breadth of C-terminal CSP-specific antibody responses may be a marker of protection.